WOMEN IN REPRODUCTIVE SCIENCE: My WOMBan's life: understanding human endometrial function. Issue 6 (December 2019) - Salamonsen, Lois A
Abstract : The focus of my life in science has been to improve reproductive health for women, with an emphasis on the endometrium, the most dynamic tissue in the human body: its remarkable cyclical remodelling is essential for the establishment of pregnancy. The most notable events in a woman's endometrial cycle are menstruation and endometrial repair, regeneration of the endometrium during the proliferative phase, attainment of receptivity by the mid-secretory phase of the cycle and the embryo–maternal interactions that initiate peri-implantation events within the microenvironment of the uterine cavity. I have contributed to understanding the molecular and cellular changes underpinning these events, and how disturbance of them leads to menstrual disorders, infertility and endometrial diseases including abnormal uterine bleeding, endometriosis and endometrial cancer. My team has contributed to changes in clinical IVF practice, to a new diagnostic for endometrial receptivity in infertile women and to enhancing endometrial repair. I have shared my world with many amazing younger scientists: it has indeed been a privileged journey.